Influence law and determination method of jack lifting load on existing station settlement - Shengzhi Wu; Xueyu Zhang; Zichen Lin; Jun Wang; Fengchun Zhang; Hongji Gao (Case Studies in Construction Materials)
The proximity of a tunnel to an existing station renders it susceptible to settlement. Jack lifting is a common method for mitigating the settlement at such stations during tunnel construction. This study investigates the mechanical responses of structures subjected to jack lifting based on case studies, numerical simulations, and theoretical analyses. These findings indicate that jack lifting significantly elevates the station structure. However, upon removing the lifting load, the station experienced resettlement. A lower initial support stiffness was correlated with increased settlement. Settlement control was achieved using a combination of active jacking and passive support. Effective jack lifting relies on addressing both advanced. A large jack load reduces the settlement of an existing structure; however, excessive loading can cause structural uplift. Therefore, the relationship between lifting load and displacement must be considered during jack lifting. Utilizing the elastic foundation beam theory, a correlation between the settlement of the existing structure and the jack-lifting load was derived, thus facilitating bidirectional control of force and displacement during the jacking process. The results offer valuable insights into the control of jack lifting in existing structures beneath tunnels.